The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1362168813519373
|View full text |Cite
|
Sign up to set email alerts
|

The noticeability and effectiveness of corrective feedback in relation to target type

Abstract: This quasi-experimental study investigated the noticeability and effectiveness of three corrective feedback (CF) techniques (recasts, prompts and a combination of the two) delivered in the language classroom. The participants were four groups of high-beginner college level francophone learners of English as a second language (ESL) ( n = 99) and their teachers. Each teacher was assigned to a treatment condition that fit his CF style, but the researcher taught the controls. CF was provided to the learners in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 58 publications
(97 reference statements)
2
40
2
Order By: Relevance
“…More easily noticed and lead to more uptake (Ammar and Spada 2006;Kartchava and Ammar 2014;Mackey and Oliver 2002;Nassaji 2007;Trofimovich et al 2007) . Elicitations create more engagement (Lyster 2004;Nassaji 2007) .…”
Section: Effectiveness Of Promptsmentioning
confidence: 99%
“…More easily noticed and lead to more uptake (Ammar and Spada 2006;Kartchava and Ammar 2014;Mackey and Oliver 2002;Nassaji 2007;Trofimovich et al 2007) . Elicitations create more engagement (Lyster 2004;Nassaji 2007) .…”
Section: Effectiveness Of Promptsmentioning
confidence: 99%
“…Other studies also show that the length of instruction may be a decisive variable. For example Erlam and Loewen (2010) applied one-hour of CF instruction and Kartchava and Ammar's (2014a) feedback sessions took only two hours and none of these studies found a positive effect for CF on the acquisition process.…”
Section: ) L1mentioning
confidence: 99%
“…In another respect, Kartchiva and Ammar (2014) found that the effects of CF were associated with target types. For example, in their experiment they found that learners were quicker on the uptake of feedback on past tense errors than on problems with questions in the past.…”
Section: Previous Studiesmentioning
confidence: 99%